Masalah Regulasi Program Merdeka Belajar-Kampus Merdeka Dalam Mendesain Pelajar Berintegritas - Saleh, Muhamad; Tanjung, Afriansyah (Jurnal Hukum IUS QUIA IUSTUM, 2024)
Among the efforts to overcome the obstacles that hinder Indonesia's future is by implementing the Merdeka Belajar Kampus Merdeka (MBKM, Independent Education Independent Campus) program, in which one of these activities is to improve interpersonal skills (soft skills) and technical skills (hard skills) in order to provide bargaining power for prospective workers in the global job market. Currently, Indonesia does not lack intelligent (literate) people or lack of skills as labor capital but is actually lacking in terms of integrity, thus the fundamental problem of the MBKM program is how to contribute in the development of the students' integrity by mapping the activity design that is deemed relevant for students with integrity within the framework of the MBKM programs. A mixed legal research methodology was chosen for this study, with secondary data serving as a complement to primary data. Primary legal materials consist of laws and regulations, supplemented by field data obtained through interviews with key informants. All data collected will be analyzed using legal and conceptual approaches. First, there are four problems with the MBKM activities in an effort to shape students with integrity, namely problems with learning outcomes which in several MBKM programs are disoriented as the MBKM program is not fully in line with the RPJMN on (HR); the other problem is the fact that the MBKM program has not been integrated with the student program related to Pancasila. Second, the design of the integrity student program in MBKM activities, namely: a) the integrity student program is added to become one of the MBKM programs; b) the integrity student program is mainstreamed in the higher education curriculum by including the public integrity learning that is collaborated on civic education, ethics, history, and business courses; and integrated with learning outcomes.Keywords: Students with Integrity, Independent Campus, MBKM AbstrakMenyelesaikan kendala yang mengikat masa depan Indonesia salah satunya caranya dengan penerapan program Merdeka Belajar Kampus Merdeka (MBKM), salah satu dari kegiatan tersebut meningkatkan kemampuan interpersonal (soft skill) dan secara teknis (hardskill) untuk memberikan dorongan daya tawar bagi calon pekerja di pasar/bursa kerja global. Saat ini Indonesia tidak kekurangan masyarakat yang cerdas (literat) atau kurangnya kemampuan sebagai modal tenaga kerja namun sejatinya kurang dalam aspek integritas, permasalahan mendasar dari program MBKM adalah bagaimana memberikan kontribusi terhadap integritas pelajar dan desain kegiatan seperti apa yang relevan antara pelajar berintegritas dalam kegiatan MBKM. Metodologi penelitian hukum campuran dipilih dalam penelitian ini, data sekunder menjadi data pelengkap dari data primer, bahan hukum primer beruapa peraturan perundang-undangan, dilengkapi dengan data lapangan melalui wawancara kepada narasumber sebagai informan kunci (key informant), semua data yang telah diperoleh akan dianalisis menggunakan pendekatan perundang-undangan dan konseptual. hasil penelitian Pertama, terdapat empat permasalahan kegiatan BKM dalam upaya menciptakan pelajar berintegritas yaitu: adanya problematika terhadap luaran pembelajaran; beberapa program MBKM disorientasi; program MBKM tidak sepenuhnya sejalan dengan RPJMN tentang SDM; program MBKM belum terintegrasi dengan program pelajar Pancasila. Kedua, desain program pelajar berintegritas dalam kegiatan MBKM yaitu: a) program pelajar berintegritas ditambah menjadi salah satu program MBKM; b) program pelajar berintegritas di arus utamakan dalam kurikulum pendidikan tinggi dengan memasukkan pembelajaran integritas publik yang dikolaborasikan pada matakuliah pendidikan kewarganegaraan, etika, sejarah, dan bisnis; dan diintegrasikan dengan learning outcomes.Kata Kunci: Pelajar Berintegritas, Kampus Merdeka, MBKM